The informational potential of typography in the dissemination of the Anthropophagic idea of cultural identity, as pictorially represented on the covers of São Paulo magazines (1928–1939) - Coelho Siqueira, Leonardo; da Costa Braga, Marcos (InfoDesign, 2025)
This paper presents a typographic analysis that aims to understand the informational potential of typography to disseminate the Anthropophagic idea of Brazilian cultural identity. This notion is exemplified on the covers of São Paulo’s magazines dedicated to ideation and culture from 1928 to 1939. The lettering on the covers of four magazines was subjected to close analysis, with the study drawing upon the principles of pictorial graphic language and microhistory. The results suggest that, at the time, typography played a significant communicative role in representing Brazilian cultural identity as well as assimilating the ideas propagated by Oswaldian Anthropophagy.